Trait self-control and the avoidance of temptation. (February 2015) - Ent, Michael R.; Baumeister, Roy F.; Tice, Dianne M.
Highlights: High trait self-control (TSC) was positively correlated with avoiding temptation. People high (vs. low) in TSC were more likely to avoid distraction. People high in TSC avoid, rather than merely resist, goal-inhibiting impulses. Abstract: High trait self-control has been traditionally described as a keen ability to resist temptation. The present research suggests that high trait self-control is linked to avoiding, rather than merely resisting, temptation. People high in trait self-control reported engaging in behaviors thought to minimize (or avoid) temptation to a greater extent than people low in trait self-control (Study 1). People high in trait self-control were more likely than those low in trait self-control to choose to work in a distraction-free environment rather than in a distracting, yet appealing, one (Studies 2 and 3).